2017
DOI: 10.1186/s12885-017-3694-6
|View full text |Cite
|
Sign up to set email alerts
|

PTTG1-interacting protein (PTTG1IP/PBF) predicts breast cancer survival

Abstract: BackgroundPTTG1-interacting protein (PTTG1IP) is an oncogenic protein, which participates in metaphase-anaphase transition of the cell cycle through activation of securin (PTTG1). PTTG1IP promotes the shift of securin from the cell cytoplasm to the nucleus, allowing the interaction between separase and securin. PTTG1IP overexpression has been previously observed in malignant disease, e.g. in breast carcinoma. However, the prognostic value of PTTG1IP in breast carcinoma patients has not previously been revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
(44 reference statements)
1
20
0
Order By: Relevance
“…The mean expression level of FOXM1 was previously reported to be the highest in the TNBC subtype, which was associated with poor prognosis and reduced survival time in patients with breast cancer (29,30). Notably, PTTG1 is an oncogene that is important for the progression of mitosis in the metaphase-anaphase transition (31,32). Additionally, PTTG1 overexpression is associated with malignancy, particularly thyroid, breast and colorectal carcinoma (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean expression level of FOXM1 was previously reported to be the highest in the TNBC subtype, which was associated with poor prognosis and reduced survival time in patients with breast cancer (29,30). Notably, PTTG1 is an oncogene that is important for the progression of mitosis in the metaphase-anaphase transition (31,32). Additionally, PTTG1 overexpression is associated with malignancy, particularly thyroid, breast and colorectal carcinoma (32).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, PTTG1 is an oncogene that is important for the progression of mitosis in the metaphase-anaphase transition (31,32). Additionally, PTTG1 overexpression is associated with malignancy, particularly thyroid, breast and colorectal carcinoma (32). A previous study indicated that PTTG1 is highly expressed in patients with breast cancer and that the expression levels were correlated with the degree of malignancy in breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Pituitary tumor-transforming 3, pseudogene (PTTG3P), is a processed pseudogene that shows high homology to its family members, pituitary tumor-transforming 1 (PTTG1) and -2 (PTTG2) 8 . Numerous investigations have shown that PTTG1 and -2 serve as two key oncogenes in a variety of human cancers, including breast cancer,9, 10 lung cancer, 11 pituitary adenoma, 12 and esophageal squamous cell cancer 13 . However, there are only a few reports regarding the expression and roles of PTTG3P in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…PTTG1-interacting protein (PTTG1IP), which is an oncogenic protein regulated the cell cycle with PTTG1. In thyroid cancer, PTTG1IP acted as a suppressor of p53 to affect the tumorigenesis [ 53 , 54 ]. According to the results of the betweenness and survival analysis in four disease types, LAMC2, GSN, and HIPK2 may respectively be the potential regulator in cell lines with grade 2 carcinoma, grade 3 carcinoma, and transitional cell carcinoma lymphatic metastasis.…”
Section: Discussionmentioning
confidence: 99%